2015
DOI: 10.1016/j.cca.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of post-heparin and pre-heparin lipoprotein lipase and hepatic triglyceride lipase on remnant lipoprotein metabolism

Abstract: LPL activity and concentration were inversely and significantly correlated with the particle size of RLP in both the post-heparin and pre-heparin plasma. Those results suggest that LPL concentration in pre-heparin plasma can take the place of LPL activity in the post-heparin plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
5
26
0
Order By: Relevance
“…These results suggested that an increase of LPL is associated with an increase of remnant lipoproteins. However, we recently reported that the amount of LPL present per RLP particle was inversely correlated with the RLP-TG or RLP-LPL/ RLP-TG ratio (reflecting particle size) [26,33]. This means that RLP with large particle size may be the result of insufficient hydrolysis of TG-rich lipoproteins by LPL on the endothelium after fat intake.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results suggested that an increase of LPL is associated with an increase of remnant lipoproteins. However, we recently reported that the amount of LPL present per RLP particle was inversely correlated with the RLP-TG or RLP-LPL/ RLP-TG ratio (reflecting particle size) [26,33]. This means that RLP with large particle size may be the result of insufficient hydrolysis of TG-rich lipoproteins by LPL on the endothelium after fat intake.…”
Section: Discussionmentioning
confidence: 97%
“…The LPL plasma concentration was measured using a novel LPL-ELISA developed at Immuno-Biological Laboratories (IBL) [26]. This is a solid phase sandwich ELISA using 2 kinds of highly specific monoclonal antibodies against human recombinant LPL.…”
Section: The Sandwich Lpl-elisa Proceduresmentioning
confidence: 99%
“…50 This effect remained significant after adjustment for blood pressure, diabetes, smoking, body mass index and LDL-C but not after additional adjustment for high-density HDL-C or TG. 50 Recently, Shirakawa et al 51 developed a new highsensitivity LPL measurement system using two different antihuman LPL monoclonal antibodies (Figure 1(b)). They found that remnant-like particles associated with cholesterol (RLP-C) or triglycerides (RLP-TG) and RLP-TG/RLP-C ratio correlated inversely with serum LPL protein concentrations.…”
Section: Studies Suggesting Serum Lpl Protein Concentration Is a Usefmentioning
confidence: 98%
“…13 The consequences are higher TG-rich VLDL synthesis and secretion from liver to circulation. 14 15 Then, LPL catalyzes the transformation of TG-rich VLDL into sdLDL, 16 promoting atherosclerosis. 17 18 Currently, postprandial hyperlipidemia is a good marker of accelerated atherosclerosis in patients with IR.…”
Section: What Are the New Findings?mentioning
confidence: 99%